Neuropil pruning in Early-Course Schizophrenia: Immunological, Clinical, and Neurocognitive Correlates - Prasad, Konasale M. (Biol Psychiatry Cogn Neurosci Neuroimaging, 2016)
INTRODUCTION: Neuropathological studies suggest neuropil reduction in schizophrenia. Altered synaptic pruning is proposed to underlie neuropil reduction. Underlying factors and clinical correlates of synaptic pruning are poorly understood. Using phosphorus magnetic resonance spectroscopy ((31)P MRS), it is feasible to assess membrane phospholipid (MPL) metabolites in the brain that specifically and sensitively reflect neuropil expansion (elevated MPL precursors) or contraction (elevated MPL catabolites). METHODS: We examined MPL metabolites and their cognitive, clinical and immunologic correlates among 28 early-course schizophrenia individuals (illness duration 1.99±1.33 years; antipsychotic-naïve=18) and 21 controls. We acquired whole-brain multi-voxel (31)P MRS data from 12 unique brain regions. Interleukin-6 and C-reactive protein (CRP) were assayed in the serum. Generalized linear mixed models examined case-control differences in MPL metabolites in these regions correcting for multiple testing. Partial correlations accounting for multiple tests examined the relationship of Interleukin-6 and CRP levels with MPL metabolite levels. RESULTS: MPL catabolite levels were increased in the thalamus in schizophrenia compared to controls. Interleukin-6 and CRP levels did not show case-control differences. Interleukin-6 levels positively correlated with MPL catabolite levels in the thalamus after correcting for multiple tests. The left thalamus MPL catabolite levels correlated negatively with sustained attention (corrected p=0.039). DISCUSSION: Elevated MPL catabolites in the thalamus suggest increased neuropil contraction that may be related to excessive synaptic pruning. The thalamic neuropil contraction is associated with Interleukin-6 levels suggesting central pathogenic mechanisms for the inflammatory mediators. Correlation of increased thalamic MPL catabolite levels with cognitive impairments suggests clinical correlates of neuropil contraction.